(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2024)
The ability to speak English in this global era is a must for those who want to achieve a better future, and this should not be the privilege of ordinary people who have access to learning English, but also to those with special needs, such as students with visual impairments in a social institution called ’Bartemeus’. The students’ physical limitation does not have to be a barrier to improve their English skills. However, the unavailability of English teachers to accommodate this is one barrier that needs a solution by providing additional English language training as well as the English teachers. Therefore, a community service (PKM) in the form of English Language Training was carried out to bridge this gap. The training was given for 10 times. and an ’eclectic’ approach was used according to the needs of the 10 visually impaired students. The interactive and communicative methods, delivered with games and songs, made the students enthusiastic and motivated to learn English. This can be seen in the final results which show the students’ level of vocabulary with an average score of above 80%. The students’ self-confidence was also increased when they studied in the classroom. This was also revealed during the evaluation given at the end of the training.